Analysis of Academic Information System Integration in Improving the Quality of Higher Education Data Reporting to PDDIKTI - Meri Mayang Sari; Untung Rahardja; Nur Azizah; Gabriel Fransiso; Jelita Bagaskara (Pandawan Sejahtera Indonesia, 2026)
Interdisciplinary Digital transformation in higher education requires integrated academic information systems to support accurate, consistent, complete, and timely reporting to the Higher Education Database (PDDIKTI). However, many universities still face reporting delays, data inconsistencies, and synchronization problems caused by fragmented systems and manual processes. This study aims to analyze the role of academic information system integration in improving the quality of higher education data reporting. A qualitative case study approach was employed at a private university in Banten Province, Indonesia. Data were collected through observation, semi structured interviews, and document anal- ysis, and analyzed using thematic analysis and the Miles and Huberman inter- active model. The findings indicate that system integration through API-based synchronization, ETL processes, automated validation, and monitoring mecha- nisms significantly improves reporting quality in terms of accuracy, consistency, completeness, and timeliness. Integration also reduces manual workloads, mini mizes data duplication, accelerates synchronization, and improves transparency in reporting activities. Nevertheless, challenges related to synchronization fail- ures, API security, and institutional interoperability remain important consider- ations. The study concludes that academic information system integration is a critical factor in strengthening higher education data governance and supporting data-driven decision-making.